Analysis of Risk Factors for Parity and age on the Incidence of Spontaneous Abortion at the Mother and Child Hospital in Makassar - Andi Sri Mutmainna; Rosdianah Rahim; Andi Irhamnia Sakinah; Sari Ifdiana Jalal; Mukhtar Lutfi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The worldwide incidence of abortion is about 35 per 100 women aged 15-44 years. Abortion is one of the causes of high maternal mortality in Indonesia from all pregnancies. Spontaneous abortion is the threat or expulsion of conception before the fetus can live outside the womb. Objective : Assess and analyze the relationship between parity and maternal age with the incidence of spontaneous abortion at Ananda Makassar Mother and Child Hospital during 2021-2022. Research Methods: This type of research is quantitative using an observational analytic research design through a case control study approach. The samples used in this study amounted to 102 case samples and 102 control samples, with a purposive sampling method. Data analysis was performed using univariate and bivariate techniques using the chi-square test. Results : The results showed that there was no relationship between parity and the incidence of spontaneous abortion with a p value of 0.123 and an OR value of 1,607 and there was no relationship between age and the incidence of spontaneous abortion with a p value of 0.344 and an OR value of 1,499. Conclusion : Parity and age do not have a statistically significant relationship with the incidence of spontaneous abortion at Ananda Makassar Mother and Child Hospital in 2021-2022.